Update on Acute Disseminated Encephalomyelitis in Children and Adolescents - Serena Massa; Adriana Fracchiolla; Cosimo Neglia; Alberto Argentiero; Susanna Esposito (Children, 2021)
Acute disseminated encephalomyelitis (ADEM) is an immune-mediated, inflammatory demyelinating disease of the central nervous system (CNS) that usually affects children and young adults after an infection or vaccination. The presence of several conditions mimicking ADEM, added to the lack of specific biomarkers, makes diagnosis potentially hard. Prompt diagnosis is necessary to start adequate treatment to improve the clinical course and long-term outcome. Because of its heterogeneity in both clinical presentation and course, challenges remain in establishing the most appropriate therapeutic approach in each patient. The aim of this review is to provide an update on management of this disease with a focus on acute treatment and to give suggestions for future research. We showed that there are currently no guidelines that help clinicians manage ADEM and therapeutic decisions are often made on a case-by-case basis. Further studies are necessary to identify clinical, laboratory, and instrumental criteria that could be correlated with outcomes and guide clinicians in choosing when and what treatment should be given in each case.